Nanotechnology in peripheral nerve repair and reconstruction - Carvalho, C. R. (2019)
The recent progress in biomaterials science and development of tubular conduits (TCs) still fails in solving the current challenges in the treatment of peripheral nerve injuries (PNIs), in particular when disease-related and long-gap defects need to be addressed. Nanotechnology-based therapies that seemed unreachable in the past are now being considered for the repair and reconstruction of PNIs, having the power to deliver bioactive molecules in a controlled manner, to tune cellular behavior, and ultimately guide tissue regeneration in an effective manner. It also offers opportunities in the imaging field, with a degree of precision never achieved before, which is useful for diagnosis, surgery and in the patientâ s follow-up. Nanotechnology approaches applied in PNI regeneration and theranostics, emphasizing the ones that are moving from the lab bench to the clinics, are herein overviewed.